Sustainable catalysis for biorefineries - Frusteri, Francesco; Aranda, Donato; Bonura, Giuseppe (RSC green chemistry series ;, 2018)
This book explores the most effective or promising catalytic processes for the conversion of biobased components into high added value products, as platform chemicals and intermediates.